Effectiveness of Problem-Based Learning Model with Canva on Fourth Grade Students' Pancasila Learning Outcomes - Eni Kumalasari; Susilo Tri Widodo (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2025)
This research is motivated by the problem of student learning outcomes which are still many below the Criteria for Achieving Learning Objectives. The factor causing the low learning outcomes of students is because teachers still use old learning models and rarely use digital learning media. The purpose of this study was to determine the effectiveness of the PBL model assisted by Canva media on student learning outcomes in Pancasila Education subjects. This type of research is experimental research with the form of Nonequivalent Control Group Design. The sample in the study amounted to 65 students from SDN Barusari 02 as a trial class, SDN Barusari 01 as an experimental class, and SDN Bulustalan as a control class. Sample determination using simple random sampling technique. Data collection was carried out using observation, interviews, documentation, and tests. The data obtained from the test results were then analyzed using the t-test (independent sample t-test) and the n-gain test. Based on the results of the t-test analysis, the tcount> ttable (3.133> 2.016) or the significance value is less than 0.05 (0.003 < 0.05) so that Ha is accepted and Ho is rejected. The n-gain test of the control class was 43.69% and showed less effective criteria. Then the N-Gain percentage in the experimental class of 61.59% shows that it is quite effective. So, it can be concluded that the application of the PBL model assisted by Canva media is effective enough to improve the learning outcomes of Pancasila Education.